A Linguistic Study of Correlative Conjunctions in English and Vietnamese Discourse - Phạm Ái Trang (2009)
The thesis is designed to investigate the semantic and syntactic features of correlative conjunctions in English and Vietnamese discourse. In order to do this, the following theoretical as well as practical matters are ….